Prevention of Labor Conflicts by Improving the Administration of Human Resources - Radeva, Veselka (Research Papers, 2020)
The article presents a part of a complex author's research with the main purpose: examining the position of employers in work conflicts in organizations. Scientific tools include developed author's methodology and the use of logistic, rational and systematic approach, as well as logic-intuitive, analytical and statistical methods. The specialized Lacord legal information system was used as the main information source, as a result of which a total of 31 152 registered labor disputes in the Republic of Bulgaria were investigated and identified for the period 2009 – 2014.The main purpose of this article is formulate and systematize norms, rules and procedures for the successful administration of human resources management activities. Recommendations from the author of the scientific study on the prevention of violations by the employers of the labor legislation in the field of changing the employment relationship are presented.
Keywords: Labor conflicts; Human resources management; Administration of human resources management; Labor law; Organizational behavior